Literature Review: Implementation of Realistic Mathematics Education (RME) Based on Concrete Media in Mathematics Learning - Musrian; Fironika Kusumadewi, Rida (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study aims to analyze the implementation of Realistic Mathematics Education (RME) based on concrete media in mathematics learning and identify research trends and development opportunities. A Systematic Literature Review (SLR) combined with bibliometric analysis was employed as the research method. Literature searches were conducted through Google Scholar, Scopus, Garuda, and Lens.org databases covering publications from 2021–2025, following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol. Of 221 identified documents, 200 were screened, 95 qualified for full review, and 20 met all inclusion criteria for in-depth analysis. Bibliometric analysis using VOSviewer software was applied to the 200 screened documents to map keyword relationships, research trends, and understudied areas, while the 20 selected articles underwent thematic synthesis to identify implementation patterns and impacts of concrete media-based RME. Findings indicate that concrete media-based RME is generally implemented through real-world contexts, hands-on media exploration, mathematization processes, and student-centered collaborative discussions. This approach has demonstrated positive impacts on conceptual understanding, mathematical reasoning, representation, problem-solving, mathematical literacy, and student engagement. Bibliometric analysis reveals that RME research remains dominated by general mathematics education studies, while the integration of RME with concrete media is still relatively scarce, representing a promising gap for future research agendas. These findings confirm that integrating RME with concrete media is a potential strategy for creating mathematics learning that is more contextual, meaningful, and responsive to students' characteristics.